A field guide to flow chemistry for synthetic organic chemists. Issue 16 (5th April 2023) - Capaldo, Luca; Wen, Zhenghui; Noël, Timothy
Abstract : This review explores the benefits of flow chemistry and dispels the notion that it is a mysterious "black box", demonstrating how it can push the boundaries of organic synthesis through the understanding of its governing principles. Abstract : Flow chemistry has unlocked a world of possibilities for the synthetic community, but the idea that it is a mysterious "black box" needs to go. In this review, we show that several of the benefits of microreactor technology can be exploited to push the boundaries in organic synthesis and to unleash unique reactivity and selectivity. By "lifting the veil" on some of the governing principles behind the observed trends, we hope that this review will serve as a useful field guide for those interested in diving into flow chemistry.